Environmental sociology - Hannigan, John A., 1948- (London ; New York : Routledge, 2006)
In this book the author argues that society's willingness to recognise and solve environmental problems rests primarily upon the claim-making activities of a number of issue entrepreneurs in science, mass-media and politics
Environmental sociology as a field of inquiry -- Contemporary theoretical approaches to environmental sociology -- Environmental discourse -- Discourse, power relations and political ecology -- Social construction of environmental issues and problems -- Media and environmental communication -- Science, scientists and environmental problems -- Risk -- Biodiversity loss : the successful 'career' of a global environmental problem -- Towards an 'emergence' model of environment and society
Includes bibliographical references (pages [154]-179) and indexes
Keywords: Environmentalism -- Social aspects